Recurrent acute pancreatitis secondary to sphincter of oddi dysfunction: Case report - Peñaloza Ramirez, Arecio (2023)
Sphincter of Oddi Dysfunction (SOD) is a rare pathology that should be considered in the differential diagnosis of patients with biliary pain episodes or recurrent acute pancreatitis and a background of cholecystectomy. Generally, these are patients with multiple consultations where this pathology has considerably affected their quality of life. Diagnosis is based on clinical findings, serological markers and supporting diagnostic tests requested according to the suspected sphincteric component. The most effective treatment is endoscopic sphincterotomy. The use of prosthesis is accepted but debated. We present the case of a male patient in his forties who consulted for multiple episodes of recurrent acute pancreatitis with etiology studies suspecting dysfunction of the pancreatic sphincter of Oddi and who was taken to endoscopic management with improvement of his clinical picture.